Reducing Unmet Need for Family Planning in Indonesia: A Policy Analysis Report - Frans, Sandra; Djasri, Hanevi (Center for Health Policy and Management, 2023)
The Indonesian government has already initiated many policies to reduce unmet need for Family Planning (FP), which is one of the three zeros commitment. It is crucial to understand whether a regulatory perspective is sufficient to solve the unmet need for family planning in Indonesia. This report explores the policy response to the unmet need of FP in Indonesia. This report draws from two sets of data. First, a document review contained 45 policies. The second set of data was qualitative interviews with the key informants collected as part of the policy analysis process of unmet need of FP. Forty five policies identified in the form of decrees, government regulations, and presidential regulations related to the unmet need for FP. Three themes emerged from the analysis: demand creation, supply side, and socio-demographic factors related to women. In the demand creation, we found varying commitments of the Provincial and District Governments in manage the FP programs. On the supply side, the government guaranteed the availability of contraceptives for all public and private health facilities, as long as they are registered in the BKKBN reporting system. However, there are still problems in distributing contraceptives, especially at the district level to the facilities. The last factors related to the unmet need for FP are the socio-demographic factors, such as fertility and socio-economic factors. In conclusion, at the national level, the policy covered has been adequate to address the demand creation and supply side, but not many about couple factors. The success of FP programs depends on the local government's strong commitment to including the unmet need of FP as their strategic plans